Integrated Soil, Water and Nutrient Management for Sustainable Rice-Wheat Cropping Systems in Asia. - IAEA (IAEA TECDOC Series No. 1802., 2016)
"The rice-wheat system is the predominant cropping system in Asia, providing food, employment and income, ensuring the livelihoods of about one billion resource poor people. However, the productivity of the current rice-wheat systems is seriously threatened by increasing land degradation and scarcity of water and labour, inefficient cropping practices and other emerging socioeconomic and environmental drivers. Responding to the need to develop alternate crop establishment methods and improved cropping practices, this publication summarizes the results from a joint FAO/IAEA coordinated research project on optimizing productivity and sustainability of rice-wheat cropping systems. It provides relevant information on how to modify existing water and nutrient management systems and improve soil management in both traditional and emerging crop establishment methods for sustainable intensification of cereal production in Asia."--Publisher's description.